Peningkatan Hasil Belajar Siswa Kelas IV Sekolah Dasar Negeri 2 Karangbener Menggunakan Model Think Pairs Share - Dwi Wahyu Arukah; Irfai Fathurohman; Moh. Syaffruddin Kuryanto (EduBase : Journal of Basic Education, 2020)
This study aims to improve the learning outcomes of grade IV students of SDN 2 Karangbener on the theme of my goals using the Think Pair Share (TPS) model. This type of research is a class action research consisting of four stages, namely planning, implementation, and reflection which is carried out for 2 cycle consists of 2 meetings. The subjects of this study were the fourth grade students of SDN 2 Karangbener with a total of 14 students. Data collection techniques using interviews, observation, tests, and documentation. Analysis of the data used is quantitative data and qualitative data. The results showed an increase in learning outcomes in the realm of knowledge. In cycle I the knowledge domain of grade IV SDN 2 Karangbener students obtained a percentage of completeness of 64.2% with the statement of students who received a total score of 9 students and those who did not complete as many as 5 students. And to be 85.7% in the second cycle with the statement of students complete marks and 2 students who did not complete. Based on the result of the class action research conducted it can be concluded that the application of the Think Pair Share (TPS) model can improve the learning outcomes of grade IV students of SDN 2 Karangbener on the theme of My Goals Abstrak Penelitian ini bertujuan untuk meningkatkan hasil belajr siswa kelas IV SDN 2 Karangbener pada tema Cita-citaku dengan menggunakan model Think Pair Share (TPS). Jenis penelitian ini adalah Penelitian Tindakan Kelas yang terdiri dari empat tahap yaitu perencanaan, pelaksanaan, pengamatan, dan refleksi yang dilaksanakan selama 2 siklus. Setiap siklusnya terdiri dari 2 pertemuan. Subjek penelitian ini adalah siswa kelas IV SDN 2 Karangbener yang berjumlah 14 siswa. Teknik pengumpulan data menggunakan wawancara, observasi, tes, dan dokumentasi. Analisis data yang digunakan yakni data kuantitatif dan data kualitatif. Hasil penelitian menunjukkan peningkatan hasil belajar pada ranah pengetahuan. Pada siklus I ranah pengetahuan siswa kelas IV SDN 2 Karangbener memperoleh persentase ketuntasan sebesar 64,2% dengan keterangan siswa yang mendapat nilai tuntas sebanyak 9 siswa dan yang tidak tuntas sebanyak 5 siswa. Dan menjadi 85,7% pada siklus II dengan keterangan siswa yang mendapat nilai tuntas sebanyak 12 siswa dan yang tidak tuntas sebanyak 2 siswa. Berdasarkan hasil penelitian tindakan kelas yang dilakukan dapat disimpulkan bahwa penerapan model Think Pair Share (TPS) dapat meningkatkan hasil belajar siswa kelas IV SDN 2 Karangbener pada tema Cita-citaku.